Characterisation of amorphous carbon films deposited using ECR-CVD - Wu, Yangsheng. (2008)
Hydrogenated diamond-like carbon (DLC) films have received a considerable amount of interest recently due to their unique characteristics such as chemical stability, mechanical hardness and high optical transparency. Among different deposition methods, the electron cyclotron resonance chemical vapour deposition (ECR-CVD) technique has been increasingly used for the growth of DLC films due to its capable of producing a highly excited plasma with greater efficiency in the breaking of the C-H bonds in the reactant gas mixture.